Associations between flame retardant applications in furniture foam, house dust levels, and residents' serum levels. (October 2017) - Hammel, Stephanie C.; Hoffman, Kate; Lorenzo, Amelia M.; Chen, Albert; Phillips, Allison L.; Butt, Craig M.; Sosa, Julie Ann; Webster, Thomas F.; Stapleton, Heather M.
Abstract: Polyurethane foam (PUF) in upholstered furniture frequently is treated with flame retardant chemicals (FRs) to reduce its flammability and adhere to rigorous flammability standards. For decades, a commercial mixture of polybrominated diphenyl ethers (PBDEs) called PentaBDE was commonly applied to foam to fulfill these regulations; however, concerns over toxicity, bioaccumulation, and persistence led to a global phase-out in the mid-2000s. Although PentaBDE is still detected in older furniture, other FR compounds such as tris(1, 3-dichloroisopropyl) phosphate (TDCIPP) and Firemaster® 550 (FM550) have been increasingly used as replacements. While biomonitoring studies suggest exposure is widespread, the primary sources of exposure are not clearly known. Here, we investigated the relationships between specific FR applications in furniture foam and human exposure. Paired samples of furniture foam, house dust and serum samples were collected from a cohort in North Carolina, USA and analyzed for FRs typically used in PUF. In general, the presence of a specific FR in the sofa of a home was associated with an increase in the concentration of that FR in house dust. For example, the presence of PentaBDE in sofas was associated with significantly higher levels of BDE-47, a major component of PentaBDE, in house dust (10 β = 6.4, p < 0.001). A similar association was observed with a component of FM550, 2-ethylhexyl-2, 3, 4, 5-tetrabromobenzoate (EH-TBB), with levels that were approximately 3 times higher in house dust when FM550 was identified in the sofa foam (p < 0.01). These relationships were modified by dust loading rates in the living room and the ratio of sofa size to room size. Interestingly, levels of TDCIPP and tris(1-chloro-2-isopropyl) phosphate (TCIPP) were also higher in dust with detections in sofa foam; however, these associations were not statistically significant and may suggest there are other prominent sources of these compounds in the home. In addition, the presence of PentaBDE in sofa foam was associated with significantly higher levels of BDE-47 in serum (p < 0.01). These results suggest that FR applications in sofas are likely major sources of exposure to these compounds in the home. Highlights: PentaBDE and FM550 in foam is associated with higher levels in dust. Foam-dust associations were not observed for TDCIPP and TCIPP. Sofa footprint in the living area and dust loading rates modified associations. PentaBDE in foam was significantly associated with higher BDE-47 in serum.